THE EFFECT OF AGRICULTURAL FINANCING ON THE WELFARE LEVEL OF OIL PALM FARMERS IN ACEH TAMIANG REGENCY - Sihotang, Mutiah Khaira (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to see the effect of agricultural financing on the welfare level of oil palm farmers in Aceh Tamiang Regency. This research method uses quantitative research with primary data types. The population in this study were all oil palm farmers who received agricultural financing. The sampling technique using the accidental sampling technique is a sampling technique based on chance, that is, anyone who meets by chance with the researcher can be used as a sample. The number of samples used in this study were 30 people. The results of the study stated that murabahah financing had a significant effect on the welfare level of oil palm farmers in Aceh Tamiang Regency with tcount ttable, namely 2,532 2,042 with a significance level of 0.01.